Grid integration and a power quality assessment of a wave‐energy park. Issue 4 (14th August 2019) - Parwal, Arvind; Fregelius, Martin; Leijon, Jennifer; Chatzigiannakou, Maria; Svensson, Olle; Strömstedt, Erland; Temiz, Irina; de Oliveira, Janaina Goncalves; Boström, Cecilia; Leijon, Mats
Abstract : This study presents a step toward the grid connection of a wave‐energy park through an electric power conversion system (EPCS) developed and installed for the wave‐energy harvesting in Lysekil, Sweden. The EPCS comprises a rectifier, a DC bus, and an inverter followed by a harmonic filter (HF). The higher‐ and lower‐order harmonics injected by the inverter in a power quality context are investigated. The lower‐order voltage harmonics partially distort the voltage‐source inverter output grid current. A phase‐locked loop‐based (PLL) grid‐phase tracking is used to attenuate the lower‐order harmonics by reflecting the grid harmonics in the inverter output. An expression for the grid‐current harmonics as a function of the grid‐voltage harmonics has been derived and implemented. A mathematical model is derived to obtain a transfer function for the PLL, and finally, proportional–integral gains are tuned for stable system operation. An HF for mitigating the higher‐order harmonics has been implemented. The total harmonic distortion is evaluated experimentally, and the results fulfil the grid‐code requirements at various frequencies and harmonic orders.